Application of optimization techniques to determine parameters of the Vibe combustion model - Prah, Ivo (Strojniški vestnik, 2009)
The capability of the optimization algorithms employed for tuning parameters of the Vibe combustion model included in 1-D thermodynamic engine cycle simulation tool AVL BOOST is analyzed while simulating high pressure phase of the in-cylinder process. The objective of the analysis includes the ability check of the optimization methods to determine the parameters of the Vibe combustion model within the tolerance range needed to set up a high fidelity model and to reach accuracy threshold of the commonly applied analytic approach for determining combustion parameters. The employed method presents an influence of different merit functions and constraints on the accuracy of the results and proposes the methodology for their quality analzsis. It can be concluded that the accuracy of the results calculated by combustion parameters determined by the optimization techniques reaches accuracy of the results calculated by a special analytically based software tool.
Keywords: motorji z notranjim izgorevanjem; izgorevanje; optimizacija